Atmospheric tritium concentrations under influence of AREVA NC La Hague reprocessing plant (France) and background levels. (October 2017) - Connan, O.; Hébert, D.; Solier, L.; Maro, D.; Pellerin, G.; Voiseux, C.; Lamotte, M.; Laguionie, P.
Abstract: In-air tritium measurements were conducted around the AREVA NC La Hague reprocessing plant, as well as on other sites that are not impacted by the nuclear industry in northwest of France. The results indicate that the dominant tritium form around the AREVA site is HT (86%). HT and HTO levels are lower than 5 and 1 Bq. m −3 for hourly samples taken in the plume. No tritiated organic molecules (TOM) were detected. 26 measurement campaigns were performed and links were established between near-field 85 Kr, HT and HTO activities. Environmental measurements are in line with those taken at the discharge stack, and tend to demonstrate that there are no rapid changes in the tritium forms released. Out of the influence of any nuclear activities, the levels measured were below 13 mBq.m −3 for HT and 5 mBq.m −3 for HTO (<0.5 Bq. L −1 ). HTO level in air seems to be influenced by HTO activities in surrounding seawater. Highlights: Measurements of 3 H in air around reprocessing plant. Measurements of 3 H background in air. Determination of chemicals forms. HT are the predominant form (85%) of 3 H around AREVA NC.